PAPUTRI (Trigonometric Rotating Board) as an innovation to enhance mathematics learning in trigonometry - Puguh Darmawan; Aniisah Suhaa Salsabiila; Ronaldo Rafael Olivero-Acuña (Panicgogy International Journal, 2025)
This study investigates the effectiveness of the Paputri (Trigonometric Rotating Board) audio-visual aid in enhancing the quality of mathematics learning, particularly in trigonometry. Employing a qualitative case study approach, the research involved third-semester students majoring in Mathematics Education at Universitas Negeri Malang, who acted as direct users of the teaching aid. The instruments used included the Paputri media, video recordings, and field notes. Data were collected through classroom observations and interactive analysis of video documentation and evaluation notes. The findings reveal that the integration of Paputri in trigonometry instruction effectively promotes students’ critical thinking, engagement, and conceptual understanding. Moreover, it fosters a more interactive and enjoyable learning environment that motivates students to actively participate in the learning process. These results highlight the pedagogical potential of manipulative and visual media in supporting mathematics learning. In conclusion, the use of Paputri as an audio-visual aid has a positive impact on students’ comprehension of trigonometric concepts. The study recommends that mathematics teachers incorporate similar innovative media in trigonometry teaching to enhance student engagement and enrich learning experiences.